Legal and political hermeneutics, or, Principles of interpretation and construction in law and politics : with remarks on precedents and authorities - Lieber, Francis, 1800-1872 (Classics in legal history., 1839)
"This book discusses the legal and political system; how it is formed, run, and the ethics involved." (PsycINFO Database Record (c) 2009 APA, all rights reserved)